The drilling of Al/SiCp metal-matrix composites.: Part II - Tosun, G; Muratoglu, M (Elsevier Sci Ltd, 2004)
The wide scale introduction of metal-matrix composites (MMCs) will increase simultaneously with development in technologies. Aluminum-matrix composites are widely used for their favorable specific strength/stiffness and corrosion resistance properties. As a consequence of the widening range of applications of MMCs, the machining of these materials has become a very important subject for research. MMCs are extremely difficult to machine (turning, milling, drilling, threading) due to their extreme abrasive properties. With the projected widespread application of MMCs, it is necessary to develop an appropriate technology for their efficient and cost-effective machining. This paper deals with the surface integrity of drilled Al/17%SiC particulate MMCs. Dry drilling tests, at different spindle-speed, feed rates, drills, point angles of drill and heat treatment, were conducted in order to investigate the effect of the various cutting parameters on the surface quality and the extent of the deformation of drilled surface due to drilling. For this reason, the surface roughness of the workpiece material was investigated after drilling operations. The workpiece material was drilled in four heat treatment conditions: as-received, solution treated, and solution treated and aged for 4 and 24 h. The drills used were 5 mm diameter, and 90degrees, 118degrees and 130degrees point angles. The experiments were performed under conditions the different speeds of 260 and 1330 rpm and the feed rates of 0.08 and 0.16 mm/rev. Drilling tests were carried out using high-speed steel (HSS), TiN coated HSS and solid carbide drills. In the experimental results, it is determined that increasing drill hardness and feed rate decrease the surface roughness of drilled surface for all heat treated conditions. In addition, the optimum surface roughness was determined when the solid carbide drill tools were used on the specimens with peakaged condition. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: metal-matrix composites; drilling